Leadership behavior: A partial test of the employee work passion model. (8th March 2019) - Egan, Richard; Zigarmi, Drea; Richardson, Alice
Abstract : This study examined empirical associations between employee cognitive perceptions of leader behavior (directive behavior, supportive behavior) and leader values (self‐concern, other orientation), employee positive affect and negative affect, and employee work intentions indicative of (dis)passionate employees. An internet‐based self‐report questionnaire survey was administered to 409 employees within three private sector organizations in Australia. Structural equation modeling indicated that supportive behavior, other‐orientation, and self‐concern had respective indirect effects on work intentions through employee positive affect. Employee positive affect was a stronger predictor of employee work intentions than was employee negative affect. Implications of these findings for theory and practice are discussed.